Factors Affecting Population Composition and Social Organization of Wild Ungulates in the Chitwan National Park, Nepal - Bhattarai, Bishnu Prasad; Kindlmann, Pavel (Journal of Institute of Science and Technology, 2018)
We investigated the factors affecting group sizes and population composition of chital (Axis axis), sambar (Rusa unicolor), hog deer (Axis porcinus), northern red muntjac (Muntiacus vaginalis), wild boar (Sus scrofa) and gaur (Bos gaurus) in the Chitwan National Park in southern Nepal. The study revealed that mean group sizes were the largest for chital (winter: 13.76 and summer: 11.01), followed by wild boar (winter: 6.89 and summer: 8.51), hog deer (winter: 5.52 and summer: 6.66), gaur (winter: 4.36 and summer: 5.81), sambar (winter: 1.86 and summer: 2.45) and muntjac (winter: 1.44 and summer: 1.46). The age and sex ratio of ungulates were biased towards females in all species. This study found the highest proportion of young individuals in wild boar and the lowest in gaur. Habitat structure, presence of predators and human disturbances strongly affected group size of ungulates in this area. Larger groups of ungulates were found in less disturbed open areas with high predatory pressure, while smaller groups and solitary individuals were found in highly disturbed forest areas. We recommend that management of human disturbances inside the park and regular monitoring of the changes in the demography of ungulate populations will improve long-term conservation strategies in this park. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 156-167